1985
DOI: 10.3147/jsfp.20.173
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of extracellular substance of Vibrio anguillarum toxigenic for rainbow trout and mouse.

Abstract: An extracellular toxic substance was separated from the cell-free culture filtrate of Vibrio anguillarum (strain NCMB571).Two fractions (GI and GII + III) obtained by Sephadex G-200 chromatography following DEAE-cellulose chromatography were lethal to rainbow trout and mice. Material separated from the GI fraction by Sepharose 4B affinity chromatography (GI-A fraction) was lethal to these animals.By sodium dodecylsulfate polyacrylamide gel electrophoresis, the GI and GI-A fractions were found to be composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…Clinical symptoms shown by infected fish were similar in every case, the most common being skin ulcers, hemorrhages at the fin bases, hem orrhagic septicaemia and ocular changes. It is thought that the extracellular products (ECPs) are implicated in the virulence of V. anguillarum, as ECPs alone is lethal to fish (Umbreit and Tripp, 1975;Inamura et al, 1984;Kodama et al, 1985;Santos, 1991;Santos et al, 1991). In addition, it has been reported that the ECPs of some strains contain hemolysin, proteases and are cytotoxic to different fish cell lines (Munn, 1980;Toranzo et al, 1983;Kodama et al, 1984Kodama et al, , 1985Inamura et al, 1985;Kanemori et al, 1987;Krovacek et al, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical symptoms shown by infected fish were similar in every case, the most common being skin ulcers, hemorrhages at the fin bases, hem orrhagic septicaemia and ocular changes. It is thought that the extracellular products (ECPs) are implicated in the virulence of V. anguillarum, as ECPs alone is lethal to fish (Umbreit and Tripp, 1975;Inamura et al, 1984;Kodama et al, 1985;Santos, 1991;Santos et al, 1991). In addition, it has been reported that the ECPs of some strains contain hemolysin, proteases and are cytotoxic to different fish cell lines (Munn, 1980;Toranzo et al, 1983;Kodama et al, 1984Kodama et al, , 1985Inamura et al, 1985;Kanemori et al, 1987;Krovacek et al, 1987).…”
mentioning
confidence: 99%
“…It is thought that the extracellular products (ECPs) are implicated in the virulence of V. anguillarum, as ECPs alone is lethal to fish (Umbreit and Tripp, 1975;Inamura et al, 1984;Kodama et al, 1985;Santos, 1991;Santos et al, 1991). In addition, it has been reported that the ECPs of some strains contain hemolysin, proteases and are cytotoxic to different fish cell lines (Munn, 1980;Toranzo et al, 1983;Kodama et al, 1984Kodama et al, , 1985Inamura et al, 1985;Kanemori et al, 1987;Krovacek et al, 1987). His tological studies have shown that the bacterium causes hemorrhagic lesions in most internal organs (Chart and Munn, 1980;Richards, 1980;Ransom et al, 1984;Ming-Chen et al, 1985;Lamas, 1991).…”
mentioning
confidence: 99%
“…However, both pathogenic and non-pathogenic bacteria are often found in the prawn hepatopancreas (Ruangpan & Kitao 1991, Chang et al 1996a) and it has been suggested that their hemolytic activity may be correlated to their pathogenicity, since factors such as adhesion and invasion (Ruangpan et al 1994) have been excluded. Although there is still much disagreement about the relationship between hemolysis and pathogenicity (Inamura et al 1984, Chung & Kou 1985, Kodama et al 1985, hemocytolytic assay is still commonly used to differentiate among suspected pathogens (Ullah & Arai 1983, Lee et al 1995.…”
mentioning
confidence: 99%
“…Among them,the well-characterized virulence prop erty of L.anguillarum is the ability to sequester iron from high-affinity iron-binding proteins of a host via a plasmid-encoded mechanism (Crosa, 1980;Actis et al, 1986).Extracellular products such as toxin, hemolysin, and proteolytic enzymes are also thought to be involved in the virulence. Tissue damage from vibriosis is caused by extracellular substances of the organism (Kodama et al, 1984;Kodama et al,1985;Krovacek et al,1987;Santos et al, 1991). Metallo protease is known to be one of these extracellular products (Inamura et al,1985;Norqvist et al,1990;Farrel andCrosa, 1991, Milton et al,1992;Stensvag et al,1993).…”
mentioning
confidence: 99%